Enhancing Thermal Comfort in Urban Communities with Urban Configurations and Green Coverage: A Case Study of Dubai Sustainable City - MUAILEQ, LAMA SULIMAN ABU (2017)
In response to the United Nations Sustainable Development Goals and the United Arab Emirates’ long-term vision for cities that provide successful and comfortable sustainable living, it is essential to study and explore strategies that enhance outdoor thermal comfort and indoor energy consumption that meets environmental, social and economic sustainability goals. The case study for this research, the Dubai Sustainable City residential cluster, which is the first development of its type and which complies with Dubai’s green building code, was chosen because it contains five clusters typical in their design and content. The software simulation analysis method was used to conduct the research, which involved using ENVI-met to build a virtual model representing the base existing case after collecting weather data from a site visit on 23 June and from records held by the National Centre of Meteorology. This model was used to evaluate the thermal behaviour of outdoor urban spaces in four phases. In the fifth phase, indoor energy was studied through simulation by using Design Builder to create a virtual model of the architectural units that were the subject of the study. The findings indicate that the layout orientation of the master plan has a significant effect on air temperature, wind speed and wind distribution within the site. Wind speed and distribution further affect the relative humidity of outdoor areas and influence user satisfaction. Moreover, courtyard design impacts air distribution and air temperature, which is connected to predicted mean vote values, and green coverage percentage in the courtyard impacts microclimate variables, as it reduces air temperature by increasing relative humidity to a moderate level. Finally, all previous enhancements applied to the outdoor thermal comfort variable affects the indoor total energy consumption, as it reduces the energy load needed to mitigate the outdoor environment.